Regulasi Diri Penganut Ajaran Ki Ageng Suryomentaraman - Musta'in Musta'in; Mochamad Widjanarko (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The Javanese people have a religious and godly character, as can be seen from historical facts that they believe in a God who protects and protects each other, thus giving rise to inner peace, which combines belief or mysticism. In this way, harmonious relationships can be established with each other to respect each other and not hurt each other. This influences self-regulation, which is a personality process in which individuals try to control thoughts, feelings, impulses and desires from external stimuli so that they are in line with their goals and aspirations. The aim of this research is to provide an understanding of self-regulation, especially for adherents of KAS teachings. This research uses a qualitative research method with a phenomenological approach. The results show that: First, after carrying out self-regulation by following KAS teachings, they felt better in controlling themselves when facing life problems. Second, feel happier and get many benefits after carrying out this self-regulation. Lastly, feeling much better after implementing self-regulation and supporting environmental factors.